A Review about the role of Psychological Contract in Affective Commitment and Turnover Intentions of Employees - Gardia, Akanksha; Goyal, Shikha (International Journal of Psychosocial Rehabilitation, 2020)
Job security, job satisfaction is some of the major facets which enable people (employees) to be loyal towards their organization and the supervisor. The loyalty originated from this facet leads to commitment towards the organization, supervisor and towards the work assigned by them. In the absence of this, employees are more likely to prefer external mobility. Psychological contract highlights modern parameters of job security, satisfaction and commitment. This contract explains the aspects, which are fortunate in harnessing the loyalty of employees towards organization, employer or supervisor and work. The major causes of conducting this study is, initially to have a pool of articles which signify the role of psychological contract in the loyalty and leaving resolution of employees and lastly to identify the circumstances in which future research can be performed.